Analysis of Financial Report Transformation in Improving the Quality of Financial Report Information Hajj Tenry Digital Printing - Nurul Najmiatul Islamiyati; Ashar Muhammad (ABM: International Journal of Administration, Business and Management, 2025)
Financial reporting transformation is a crucial requirement for Micro, Small, and Medium Enterprises (MSMEs), particularly in improving the accuracy, efficiency, and quality of the information presented. Accurate financial reporting plays a crucial role in supporting decision-making, business planning, resource management, and improving access to financing. This study aims to examine the transformation of accurate financial reporting in accordance with Financial Accounting Standards (SAK) at Haji Tenry Digital Printing. The method used in this study is descriptive. Data collection techniques were conducted through interviews, observations, and documentation of financial recording and reporting activities before and after the transformation. The results show that before the transformation, financial recording was still done manually using cash books and physical notes, making it susceptible to recording errors, lost documents, and delays in report preparation. After the transformation using the SIAPIK application, the recording process became more orderly, accurate, and efficient. In addition, this transformation also increases business actors' awareness of the importance of financial reporting in making more appropriate business decisions. Digitizing financial reporting systems has been proven to accelerate work processes, improve information reliability, and help business owners understand their overall financial condition. In conclusion, the use of the Financial Information Recording Application Information System (SIAPIK) has a positive impact on the quality of financial reporting information. It is recommended that this system be implemented continuously, along with training for staff to ensure optimal application utilization.